Pengaruh Terapi Though Stopping Terhadap Peningkatan Kualitas Tidur Lanjut Usia di Balai Sosial Lanjut Usia Mandalika NTB - Awan Dramawan; Muhammad Muttaqin; Ely Mawaddah; Cembun Cembun (Poltekkes Kemenkes Mataram, 2021)
The need for sleep is a basic need in human survival, especially for the elderly as a population at risk and in dire need of good sleep quality, most of the elderly experience poor sleep quality so that the choice of Thought Stopping therapy in addition to reducing anxiety also has an effect short-term positives such as relaxation, improved sleep quality, reduced mood and negative thoughts. This study aims to provide an overview of improving the sleep quality of the elderly who receive Thought Stopping therapy. This study design is a quasi-experimental pre-posttest with Thought Stopping therapy intervention. The sample was was 30 elderly people who experienced poor sleep quality at BSLU Mandalika NTB and taken using purposive sampling technique. The results of Wilcoxon test showed p-value = .000 which means that there is an effect of Thought Stopping therapy on improving the sleep quality of the elderly at BSLU Mandalika NTB. It can be concluded that Thought Stopping therapy is effective in improving sleep quality. This study results suggest the application of Thought Stopping therapy as an intervention to improve the sleep quality of the elderly.